Critical success factors for concrete recycling in construction projects - Badraddin, Abdulmalek Khaled Mohammed; Afiqah R., Radzi; Almutairi, Saud; Rahimi, A. Rahman (MDPI, 2022)
This study explores the success factors of concrete recycling in construction projects, using Malaysia as a case study. The objectives include (1) identifying the critical success factors for concrete recycling in construction projects, (2) comparing the critical success factors between large enterprises (LEs) and small–medium enterprises (SMEs), and (3) developing constructs that group the critical success factors. First, a list of success factors was identified through semi-structured interviews with fifteen construction industry professionals and a systematic literature review of journal articles. This list was then incorporated into a questionnaire and disseminated to industry professionals. Eighty-nine valid responses were collected and analyzed using mean score ranking, normalization, agreement analysis, and factor analysis techniques. The analyses showed ten critical success factors for concrete recycling. The critical success factors include the availability of uniform standards for concrete recycling, adequate awareness among project stakeholders on concrete recycling, appropriate construction waste management plans, government policies to support concrete recycling, good marketing strategy for concrete recycling, good communication among employees, applications for recycled concrete in sub-industries, provisions in work method statements on concrete recycling, positive legislation toward concrete recycling, and availability of concrete recycling infrastructure. However, the percentage of agreement between SMEs and LEs for the ten critical success factors was only 22%. In other words, there is no consensus on criticality across organizational sizes. Finally, the critical success factors can be categorized into two interrelated groups: external and internal. This study contributes to the literature by analyzing the necessary success factors for concrete recycling. The study findings allow researchers and practitioners to develop strategies to promote concrete recycling.